Pelapisan Sosial pada Masyarakat Desa Pulau Mungkur Kecamatan Gunung Toar Kabupaten Kuantan Singingi - Widiya Natasari; Hesti Asriwandari (Penerbit Jurnal Indonesia, 2024)
It is undeniable that the gap in life makes a multi-layered form in society, we can find this in any community, one of which is in the community in the village of Mungkur Island. This can be seen in the daily life of its citizens, such as when the community gathers, among them there will be one or more people who are respected because of the level of education they have and because the economic level they have is better than other people. The purpose of this study is to find out which criteria are the most dominant in determining social stratification in society and to see the relationship between social stratification criteria and strata in society in Mungkur Island Village. The method in this study is quantitative inferential. The population of this study is 243, the research sample is housewives or heads of households. The data collection techniques used are questionnaires, observations and documentation. Based on the results of the study, the score for the wealth criterion was obtained 1,207, for the wealth criterion a score of 1,449, for the wealth criterion a score of 1,607, for the wealth criterion a score of 1,892. And for the relationship between wealth and social strata 0.66, the relationship between power and social strata 0.73, the relationship between honor and social strata 0.6 and the relationship between education and social strata 0.83. It can be concluded that there is no most dominant criterion among the four social stratification criteria, it turns out that these four criteria have the same strength, namely strong in Mungkur Island Village and the four social stratification criteria have an influence on social strata in society, but education has a greater influence.